(untitled) (Acta Scientiarum. Biological Sciences, 2025)
Amblyomma sculptum and Amblyomma ovale are ticks (Acari: Ixodidae) that commonly bite humans and are associated with Spotted Fever (SF). The objective of this study was to conduct a literature review of articles indexed in the Web of Science platform, published between 1992 and 2024, that report the presence of A. sculptum and A. ovale in the state of Paraná, Brazil. A total of 30 articles were reviewed, of which most (n = 14) were published by Brazilian publishers, although articles in international journals received more citations. The main topics addressed by the articles were: (i) the use of serological and molecular techniques to detect antibodies and bacteria associated with the causative agents of SF; (ii) application of questionnaires to study participants; (iii) geospatial analyses to determine risk areas; and (iv) collection of free-living ticks and those found on parasitized hosts. Of these articles, 25 reported the presence of A. ovale and A. sculptum, with the first species recorded parasitizing 26 taxonomic groups of vertebrates, while A. sculptum was recorded parasitizing 12 groups. Amblyomma ovale accounted for the highest number of parasitic ticks (n = 632), mainly adults found on carnivores. In contrast, 365 A. sculptum parasitic ticks were collected, primarily from domestic animals (e.g., dogs and horses). Notable research gaps remain, particularly in areas related to basic biology and environmental perception/education.